Moving ; Greased lightning [videorecording (DVD)] - Shore, Howard (Warner Bros. Entertainment, 2006)
Moving: The tale of a flustered suburbanite trying to relocate his family from New Jersey to Idaho. Originally released as a motion picture in 1988.